2016
DOI: 10.1021/acs.jpcc.6b03302
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Conformational Dynamics of Structurally Tuned Aryl-Substituted Terpyridyl Ruthenium(II) Complexes to Inhibit Charge Recombination in Dye-Sensitized Solar Cells

Abstract: To explore the impact of dye structure on photoinduced interfacial electron-transfer (ET) processes, a series of systematically tuned 4′-aryl-substituted terpyridyl ruthenium­(II) complexes have been studied in TiO2 film and dye-sensitized solar cell (DSSC) device settings. Structural tuning is achieved by the introduction of methyl substituents at the ortho positions of a ligand aryl moiety. Solar power conversion efficiencies are measured, and these values are deconstructed to better understand the fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 133 publications
1
24
0
Order By: Relevance
“…Furthermore, recent studies have shown that charge recombination to oxidized dyes is sensitive to the bridge that separates them from the surface or the orientation of the surface linker. 39 , 40 Indeed, specific bridge mediated pathways to oxidized dyes have been identified. 37 Taken together, these findings indicate that the observed rate constants do, at least partially, report upon the interfacial electron transfer rate constant(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have shown that charge recombination to oxidized dyes is sensitive to the bridge that separates them from the surface or the orientation of the surface linker. 39 , 40 Indeed, specific bridge mediated pathways to oxidized dyes have been identified. 37 Taken together, these findings indicate that the observed rate constants do, at least partially, report upon the interfacial electron transfer rate constant(s).…”
Section: Discussionmentioning
confidence: 99%
“… 32 38 It is possible that diffusion does rate limit interfacial electron transfer in some cases, however this does not explain the reported driving force dependencies or the recent observation of specific interfacial electron transfer pathways at sensitized TiO 2 interfaces. 39 , 40 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These measurements have shown that under coherent transport mechanism the charge-transfer rates scale as the square of the electronic coupling in biaryl compounds, and since the electronic coupling varies with the interplanar dihedral angle (f)b etween the aryl groups,t he chargetransfer rates follow as quared cosine trend with f. [5][6][7][8] Importantly,t he residence time for the charge onto biaryls is expected to be negligible in coherent charge transport using break-junction techniques. The implication of this finding in non-coherent charge-transfer rates is being investigated.…”
mentioning
confidence: 99%
“…[1][2][3][4] These measurements have shown that under coherent transport mechanism the charge-transfer rates scale as the square of the electronic coupling in biaryl compounds, and since the electronic coupling varies with the interplanar dihedral angle (f)b etween the aryl groups,t he chargetransfer rates follow as quared cosine trend with f. [5][6][7][8] Importantly,t he residence time for the charge onto biaryls is expected to be negligible in coherent charge transport using break-junction techniques. [1][2][3][4] These measurements have shown that under coherent transport mechanism the charge-transfer rates scale as the square of the electronic coupling in biaryl compounds, and since the electronic coupling varies with the interplanar dihedral angle (f)b etween the aryl groups,t he chargetransfer rates follow as quared cosine trend with f. [5][6][7][8] Importantly,t he residence time for the charge onto biaryls is expected to be negligible in coherent charge transport using break-junction techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation